Electrocardiogram interpretation of the athletic heart: Examples and resources - Dineen, E. H.; Shenkman, H.; Bourne, G.; Froelicher, V. (2021)
The American College of Cardiology`s California Chapter has established a Exercise Health & Sports Cardiology Committee in response to the growing need for evidence-based, standardized, comprehensive care for athletes. The committee aims to serve as a resource for consultative cardiovascular assessment of highly active individuals as well as a home for educational tools to aid in their assessment and management.